Implementation of the eco-tourism destination concept in community forest use: Case study at the tourism object of Gunung Dago, Parung Panjang, Bogor - Pradana, Triandi; Juliana, Mudita (Universitas Wiralodra, 2023)
This research aims to analyze the implementation of the ecotourism concept in forest utilization in the Mount Dago Tourism Area, Parung Panjang. The ecotourism concept is a sustainable approach to natural resource management that integrates nature conservation efforts, local economic development, and active participation of local communities. By implementing an ecotourism approach in forest utilization, it is hoped that balanced social, economic, and environmental benefits can be achieved. The method for conducting research uses a qualitative study approach. Collecting data sources were collected through participatory observation, interviews with various relevant stakeholders, and analysis of forest management and tourism documents. The research sample consisted of forest managers, local community members, tourism entrepreneurs, and visitors involved in this study. The results of this research provide an understanding of implementing the ecotourism concept in forest use in the Mount Dago Natural Tourism Area. These findings can be used as a basis for developing and piloting other natural tourism destinations to apply the concept of sustainable forest management with an ecotourism approach. This research also provides insight to relevant stakeholders, including forest managers, local communities, and tourism entrepreneurs, about the benefits of tourist destinations implementing the eco-tourism concept.